In vitro evaluation of the antibacterial activity of five sealers used in root canal therapy - Mohsen Hasheminia; Hamid Razavian; Hamid Mosleh; Babak Shakerian (Wolters Kluwer Medknow Publications, 2017)
Background: Antibacterial activity is one of the important characteristics of an ideal root canal sealer. The aim of this study was to investigate the antibacterial activity of five different sealers against Enterococcus faecalis using two different methods. Materials and Methods: The mineral trioxide aggregate (MTA) Fillapex, Tg-sealer, Endomethasone, AH-26, and RoekoSeal sealers were placed into the brain heart infusion (BHI) culture medium containing E. faecalis (PTCC1393). The diameter of the bacterial zone of inhibition was measured. In the direct contact test, a suspension containing grinded set sealers and E. faecalis bacteria was cultured in BHI after 6, 15, and 60 min. The number of colonies in milliliter was calculated. Data were subjected to one-way ANOVA and Tukey's multiple comparisons test (P < 0.05). Results: In the agar diffusion test, Endomethasone had the highest antibacterial activity against E. faecalis compared to other sealers (P < 0.001). In the direct test, the antibacterial effect of MTA Fillapex was significantly higher than that of all other sealers (P < 0.001). Conclusion: The technique and components of the tested sealers affect the antibacterial activity results. This study showed that all of sealers had antimicrobial effect.